Cover Feature: Inhibition by Inorganic Dopants of γ‐Alumina Chemical Weathering under Hydrothermal Conditions: Identification of Reactive Sites and their Influence in Fischer–Tropsch Synthesis (ChemCatChem 12/2017). Issue 12 (22nd June 2017) - Abi Aad, Jane; Courty, Philippe; Decottignies, Dominique; Michau, Mathieu; Diehl, Fabrice; Carrier, Xavier; Marceau, Eric
Abstract : The Cover depicts the formation of surface mixed phases and Si grafting on the lateral facets of γ ‐alumina. In their Full Paper, J. Abi Aad et al. demonstrate that formation of surface mixed phases and Si grafting on the lateral facets of γ ‐alumina respectively inhibits and suppresses the alumina transformation to boehmite through a dissolution–precipitation process under hydrothermal conditions. More information can be found in the Full Paper by J. Abi Aad et al.(DOI:10.1002/cctc.201700140 ).